Automated C-11 Methyl Iodide/Triflate Production: Current State of the Art - H. Mock, Bruce (Current Organic Chemistry, 2013)
[11C]methyl iodide was originally produced by using LiAlH4 to reduce [11C]CO2 to [11C]methanol, followed by reaction with liquid hydriodic acid. However, it is difficult to obtain the desired high specific radioactivity of the end-product 11C-methylated tracer because the lithium reagent solution is so easily contaminated by atmospheric [11C]CO2 The introduction of high temperature gas-phase methodologies greatly enhanced the specific activity of 11C-labeled PET tracers by eliminating the lithium reagent entirely. Details for three commercially available gas-phase synthesis modules are provided and discussed with respect to ease-of-operation and preventative maintenance concerns. Lastly, C-11 target performance is discussed with respect to the in-target release of carrier [11C]carbon, the remaining obstacle to ultra-high specific activity for 11C-labeled PET tracers.
Keywords: Methyl iodide